Opinion piece: ensuring an effective higher engineering provision for STEM engaged applicants. Issue 1 (1st January 2019) - Knapton, Dave
ABSTRACT: This paper is positioned at the junction between the requirements of the manufacturing industry for a significantly increased number of professionally registered engineers in the UK employment pool and the excellent work which is ongoing in and around the education sector to encourage more young people to follow a career in this field. Higher Education (HE) is a natural stepping stone between these two stakeholder areas of the skills pipeline and has an opportunity to make a unique contribution to ensure an effective HE engineering provision for Science, Technology, Engineering and Maths (STEM) engaged applicants.